Anticonvulsant Effect of Minocycline on Pentylenetetrazole-Induced Seizure in Mice: Involvement of 5-HT3 Receptor - Entezari, Zahra; Jahanabadi, Samane (Drug Research, 2022)
Minocycline, widely used as an antibiotic, has recently been found to have an anti-inflammatory, neuroprotective and anticonvulsant effects. This study was aimed to investigate the anticonvulsant effect of acute administration of minocycline on pentylenetetrazole (PTZ)-induced seizures considering the possible involvement of 5-HT3 receptor in this effect. For this purpose, seizures were induced by intravenous PTZ infusion. All drugs were administrated by intraperitoneal (i.p.) route before PTZ injection. Also, 1-(m-chlorophenyl)-biguanide (mCPBG, a 5-HT3 receptor agonist) and Tropisetron (a 5-HT3 receptor antagonist) were used 45 minutes before minocycline treatment. Our results demonstrate that acute minocycline treatment (80 and 120 mg/kg) increased the seizure threshold. In addition, the 5-HT3 antagonist, tropisetron, at doses that had no effect on seizure threshold, augmented the anticonvulsant effect of minocycline (40 mg/kg), while mCPBG (0.2 mg/kg) blunted the anticonvulsant effect of minocycline (80 mg/kg). In conclusion, our findings revealed that the anticonvulsant effect of minocycline is mediated, at least in part, by inhibition of 5-HT3 receptor.
Keywords: Minocycline; 5-HT3 receptor; Seizure Threshold; Pentylenetetrazole; Mice